Towards Generating Richer Code by Binding Security Abstractions to BPMN Task Types - Damasceno, Julio Cesar; Nezhad, Hamid Reza Motahari; Li, Jun; Northfleet, Caio; Stephenson, Bryan; da Silva Souza, André Ricardo; Albuquerque de Medeiros, Robson Wagner; Barros Silva, Bruno Leonardo; Aires Lins, Fernando Antonio; Souto Rosa, Nelson; et al. (Revista de Informática Teórica e Aplicada, 2010)
This paper presents an approach for binding security requirements to different BPMN task types to create secure executable business processes.